2006
DOI: 10.1021/jo060885i
|View full text |Cite
|
Sign up to set email alerts
|

How to Promote Sluggish Electrocyclization of 1,3,5-Hexatrienes by Captodative Substitution

Abstract: Hexatriene electrocyclization, if not disfavored by its harsh reaction conditions, can be highly useful for the synthesis of complex organic molecules. Herein we developed a two-layer ONIOM method which could predict the activation free energy of hexatriene electrocyclization with an accuracy of about 1.0 kcal/mol. Using this carefully benchmarked method, we calculated the activation free energies for a variety of substituted hexatrienes. It was found that extraordinarily rapid electrocyclization could occur f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 32 publications
3
49
0
1
Order By: Relevance
“…In the 19 F NMR spectra of reaction mixture along with minor signals of expected dye base 11 we detected signals of major product that was isolated and identified by X-ray structure analysis as compound 12. Formation of it may be explained by the elecrocyclization [35] of the system of double conjugated bonds with 6-p ē of compound 11 into appropriate cyclohexadiene followed by HF addition (Scheme 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 19 F NMR spectra of reaction mixture along with minor signals of expected dye base 11 we detected signals of major product that was isolated and identified by X-ray structure analysis as compound 12. Formation of it may be explained by the elecrocyclization [35] of the system of double conjugated bonds with 6-p ē of compound 11 into appropriate cyclohexadiene followed by HF addition (Scheme 6).…”
Section: Resultsmentioning
confidence: 99%
“…Copper (I) iodide (1.43 g, 7.5 mmol) was added all at once and the solution of stannane 4 (4.87 g, 11.25 mmol) in THF (20 ml) was slowly added over 40 min via syringe. The reaction mixture was maintained at 0 8C for 30 min, then was heated to r.t. for [30][31][32][33][34][35][36][37][38][39][40] …”
Section: -Pentafluorbuta-13-dienyl-benzothiazole (1)mentioning
confidence: 99%
“…An excellent illustration of the need to drive the development of such methodology can be found in the relative under-use of the 6p-electrocyclisation of 1,3-(Z)-5-hexatrienes in strategic synthesis. 1,2 Though not the sole factor, synthetic difficulties in obtaining the requisite 1,3-(Z)-5-hexatrienes in reliable yield and with high stereo-control have certainly limited the utility of such a reaction. To date, cis-vinylstannane and cis-vinylboronate reagents have played a major role in the construction of Z-conjugated systems via transition metal catalyzed cross coupling reactions, i.e., the Stille 3 and Suzuki 4 reactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Triene 45, however, cyclised at only 100°C to give 52 in excellent yield, the structure of which was confirmed by X-ray crystallography ( Figure 2). We attribute this reactivity to a lowering of the transition state through a capto-dative effect, [27] induced by the electronwithdrawing effect of the ketone substituent with respect to the β-carbon. Adding further to the utility of this reaction, it was found that a rearrangement of 52 could be driven at higher temperatures (Scheme 6).…”
mentioning
confidence: 99%